Range Finding Phytotoxicity Test of Lead to Mangrove Plants of Rhizophora mucronata - Lina Hanarisanty; Harmin Sulistiyaning Titah (Jurnal Teknik ITS, 2019)
Pollution of heavy metals can occurred in river and estuary area. Lead (Pb) was one type of heavy metals that was found in river and estuary area. Pb was one of the conservative heavy metals and Pb can be toxic to human being, animals and plants. The aim of this study was to determine the survival of mangrove of Rhizhophora mucronata against the Pb in range finding phytotoxicity test with various concentration of Pb. Pb in various of concentration were exposured to Rhizhophora mucronata for 7 days. Variations of Pb concentrations were 0 mg/L as control, 50 mg/L, 100 mg/L, 300 mg/L, 500 mg/L, and 700 mg/L. The physical observation was conducted during the range finding phytotoxicity test. The results showed that the Rhizophora mucronata was able to survive with Pb concentration of 100 mg/L. While the concentration of mortality (LC50) was at a concentration of 367.58 mg Pb /L. The death effects can be caused that the plants can absorb/accumulate contaminants in their bodies. In conclusion Rhizophora mucronata can survive at 100 mg/L Pb concentration.